Ofdm Optimal for Bi-Directional Communication in Smart Grid [Ofdm Óptimo Para la Comunicación Bidireccional en Las Redes Eléctricas Inteligentes] - Rodriguez-Garcia, A (Universidad de Tarapaca, 2018)
In this article is designed a system OFDM optimal for the bi-directional communication at the smart grid. The transmission is simulating a channel with noise class A, what is characteristic of the electrical lines of high, medium and low voltage. The OFDM system is optimal because they employ two-dimensional constellations rotated: rectangular, circular and hexagonal of four and sixteen symbols that have the best performance compared to their counterparts who are the constellations without rotating. The optimal OFDM decreases the likelihood of error of bits as minimum of 1x10-2 when compared with OFDM-QAM, on a channel with noise class A. © 2018, Universidad de Tarapaca. All rights reserved.